The origins of the Reference: analysis and development of the service - Cucchetti, Paolo (Bibliothecae.it, 2023)
This paper analyzes the origins and development of the reference service and how it has become the most important practice within libraries. Through a historical investigation that begins in the second half of the nineteenth century and continues beyond the middle of the twentieth century, the diffusion of this activity in its various components and ramifications is outlined, focusing on the application differences present in the various types of library institutions. The research analyzes the causes that led to the birth of this activity, which has completely revolutionized the way of perceiving libraries and their work. Using the sources of the main authors who have dealt with this topic, it is possible to understand the growth of the concept of “assistance” towards readers, its various extensions and above all the consequences that these ideas had on the evolution of the image of libraries within the society.